2017
DOI: 10.14715/cmb/2017.63.11.12
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of silver nanoparticles on Fluconazole resistant Dermatophytes identified by (GACA)4 and isolated from primary school children suffering from Tinea Capitis in Ismailia – Egypt

Abstract: Fungal infections caused by dermatophytes recently became more common. Available antifungal drugs are limited because of emergence of resistant strains due to prophylaxis with them, so there is an urgent need for novel antifungals. This study is aimed to detect the antifungal activity of silver nanoparticles (SNPs) on Fluconazole resistant dermatophytes isolated from primary school children clinically suffering from tinea capitis and attending El-Sheikh Zaid Dermatology Center in Ismailia. The study was done o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…There are various applications for nanomaterials (19)(20)(21)(22). After experimental comparison, it was found that compared with the model group, the SOD activity and GSH-Px activity in the myocardial tissue cells of the three groups injected with different diameters of CeO2 nanoparticles were remarkably increased, and the MDA content in the myocardial cells was also greatly reduced, showing statistically visible differences (P< 0.05).…”
Section: Changes Of Apoptotic Cells In Myocardial Tissue Of Rats With...mentioning
confidence: 94%
“…There are various applications for nanomaterials (19)(20)(21)(22). After experimental comparison, it was found that compared with the model group, the SOD activity and GSH-Px activity in the myocardial tissue cells of the three groups injected with different diameters of CeO2 nanoparticles were remarkably increased, and the MDA content in the myocardial cells was also greatly reduced, showing statistically visible differences (P< 0.05).…”
Section: Changes Of Apoptotic Cells In Myocardial Tissue Of Rats With...mentioning
confidence: 94%
“…There are various reports that showed the potential use of silver nanoparticles as antifungal agents [12,13] and in particular against dermatophytes [14][15][16]. Hence, the aim of this study is to formulate a nanosuspension containing surfactant based polymeric dispersion doped with the antifungal drug griseofulvin (GF)/ silver nanoparticles and test its efficacy against T. rubrum biofilms.…”
Section: Introductionmentioning
confidence: 99%